THE IMPLICATIONS OF POLITICAL ENGAGEMENT TO THE CAMPAIGN SUBSTANCE ON TWITTER: (CASE STUDY OF DEPOK CITY REGIONAL HEAD ELECTION 2020 IN INDONESIA) - Wildhan Khalyubi; Azka Abdi Amrurobbi; Moch Edward Trias Pahlevi; Muhammad Iqbal Khatami (Bawaslu Provinsi Jawa Barat, 2022)
This research aims to look at political engagement on social media which is then deepened with the substance of the campaign in the Depok City Regional Head Election in 2020. There has been no research that combines the amount of political engagement with the substance of the campaign. The regulation of the regional head election campaign in the Covid-19 situation is technically regulated in PKPU No. 13 of 2020 regarding the Second Amendment to the General Election Commission Regulation Number 6 of 2020 concerning the Implementation of the Election of Governors and Vice Governors, Regents and Vice Regents, and/or Mayors and Vice Mayors Simultaneously Continued in Non-Natural Disaster Conditions Corona Virus Disease 2019 (Covid- 19) raises a new regulatory feature in the form of the use of social media. Therefore, this regulation becomes the basis for looking at the political engagement of netizens which is then explored by looking at the substance of the campaign on social media. This research method is descriptive qualitative with data collection techniques using Social Network Analysis (SNA) precisely on Twitter social media. The findings of this study indicate that although the campaigns of candidate pairs on Twitter accounts have a high number of political engagement which obtained from netizens, this does not necessarily indicate a narrative substance in the campaign program. However, there is an atmosphere of political polarization which also contributes to the high number of political engagements on Twitter.